2019
DOI: 10.26873/svr-814-2019
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Thymoquinone in Ameliorating the Hepatoxic Effect of Diazinon in Male Rats

Abstract: Diazinon (DZN) is one of most dangerous hepatotoxic organophosphorous insecticides used in veterinary practices which induces oxidative stress. The present study aimed to evaluate the ameliorative role of thymoquinone (TQ) in diazinon toxicity. Forty nine male albino rats and were divided into seven groups (n =7 for each). The first group (c-ve group) orally received saline daily all over the experiment (8 weeks). The second group (c+ve1) orally received DZN (15 mg/kg body weight, b-w) for the first four weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 40 publications
2
3
0
Order By: Relevance
“…These adverse effects on the hematological parameters were greatly ameliorated by TQ supplementation. These results are consistent with Ghazy et al 28 , the alleviation of anemia induced by diazinon toxicity by TQ administration. The improved hematological parameters may be www.nature.com/scientificreports/ attributed to the ameliorative effect of TQ against free radicals caused by malathion inhalation 32,33 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These adverse effects on the hematological parameters were greatly ameliorated by TQ supplementation. These results are consistent with Ghazy et al 28 , the alleviation of anemia induced by diazinon toxicity by TQ administration. The improved hematological parameters may be www.nature.com/scientificreports/ attributed to the ameliorative effect of TQ against free radicals caused by malathion inhalation 32,33 .…”
Section: Discussionsupporting
confidence: 93%
“…These results are compatible with Kanu et al 27 and Ghazy et al 28 who reported that other OPs are associated with a significant decrease in the hematological parameters, especially RBCs, hemoglobin, and platelet counts, and with a significant increase in the WBCs count. Moreover, Ghazy et al 28 reported decreases in erythrocytes could be as a result of either direct erythrocytes destruction by the pesticide or indirect through its bad effects on the bone marrow. Coles 29 stated www.nature.com/scientificreports/ that low packed cell volume promotes reticulocyte released from bone marrow, which increases the MCV.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings are consistent with these results [ 77 ]. DZN was found to increase the amount of apoptotic cells in hepatic tissues and produce toxic damage to hepatocytes [ 78 ]. DZN causes mitochondrial damage by increasing membrane permeability and generating ROS [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-3 expression, an indicator of apoptosis, was also shown to be suppressed by TQ, as was previously reported that caspase-3 expression was also shown to be stifled by TQ [ 84 ]. In addition, the molecular analysis indicated that TQ inhibits apoptosis by showing a significant drop in Caspase-3 and Bax gene mRNA expression by inhibiting the release of cytochrome c, a cornerstone of the intrinsic apoptotic cascade [ 78 ].…”
Section: Discussionmentioning
confidence: 99%